امل حسين نعيثل الزيدي تحضير ودراسة بعض اوكتانات العناصر الانتقاليه واختبار كفاءتها في عملية التثبيت الحراري لبولي كلوريد الفاينيل - الزيدي, امل (University of Thi-Qar Journal of Science, 2019)
The study was included the preparation of some metal carboxylates such as Nickel and Zinc octanate ,These complexes were identified by spectroscopy methods and by elemental analysis .They were used as thermal stabilizers for PVC and study the degradation and stabilization mechanisms by used ultraviolet – visible and infrared spectroscopy ,The thermal stability of pure PVC and PVC containg different metal carboxylates was investigation by thermogravimetric analysis (TGA) .